Existence of the audit expectation gap and its impact on stakeholders' confidence: The moderating role of the financial reporting council - Taslima Akther; Fengju Xu (International Journal of Financial Studies, 2020)
This paper empirically emphasizes the existence of the audit expectation gap and its impact on stakeholders' confidence, moderated by the active role of the financial reporting council. As a maiden attempt to portray the relationship, a higher-order model has been constituted and assessed with the pragmatic exploration, smearing the partial least squares structural equation model (PLS-SEM). The data contains 174 respondents as auditors, investors, investment and credit analysts, and regulatory agencies in Bangladesh. The study explores audit expectation gap from diverse aspects, such as auditors responsibility for fraud detection, meaning, and usefulness of the audit report, auditors providing the non-audit services, auditors' responsibility for going concern reporting, and also an unmet expectation for the other assurance services, such as assurance on the other parts of the annual report beyond the financial statements, like management discussion and analysis and corporate social and environmental disclosure. The findings suggest that the audit expectation gap is negatively related to stakeholders' confidence and the greater the audit expectation gap is, the lower stakeholders' confidence is in the audit. Auditors maintaining perceived independence and improving the level of communication with users will diminish the audit expectation gap and induce stakeholders' confidence simultaneously. Moreover, the active role of the financial reporting council acts as a moderator to ensure the auditors' perceived independence. The result of the study motivates the policymakers to concentrate on the users' audit-related expectations and also intends the importance of independent audit oversight.
Keywords: 330; audit expectation gap; auditor’ s perceived independence; financial reporting council; stakeholders’ confidence